Genetic architecture of host proteins involved in SARS-CoV-2 infection - Pietzner, Maik; Wheeler, Eleanor; Carrasco-Zanini, Julia; Raffler, Johannes; Kerrison, Nicola D.; Oerton, Erin; Auyeung, Victoria P. W.; Luan, Jian’an; Finan, Chris; Casas, Juan P.; Ostroff, Rachel; Williams, Steve A.; et al. (Nature communications, 2020)
Understanding the genetic architecture of host proteins interacting with SARS-CoV-2 or mediating the maladaptive host response to COVID-19 can help to identify new or repurpose existing drugs targeting those proteins. We present a genetic discovery study of 179 such host proteins among 10,708 individuals using an aptamer-based technique. We identify 220 host DNA sequence variants acting in cis (MAF 0.01-49.9%) and explaining 0.3-70.9% of the variance of 97 of these proteins, including 45 with no previously known protein quantitative trait loci (pQTL) and 38 encoding current drug targets. Systematic characterization of pQTLs across the phenome identified protein-drug-disease links and evidence that putative viral interaction partners such as MARK3 affect immune response. Our results accelerate the evaluation and prioritization of new drug development programmes and repurposing of trials to prevent, treat or reduce adverse outcomes. Rapid sharing and detailed interrogation of results is facilitated through an interactive webserver ( https://omicscience.org/apps/covidpgwas/ ). Finding effective treatments for COVID-19 depends upon understanding genetic regulation of proteins involved in SARS-CoV-2 infection and host response. Here, the authors identify genetic variants linked to expression of such proteins, data which could lead to the discovery of therapeutic targets.